Conceptualizing features of ritual comparative phraseologisms (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
Ritual phraseologisms of the comparative origin were studied, the fact of the native speaker deep awareness of the ritual reality (donor area) and high level of the recipient area cognition were discovered. The structure with verbalizators of consept-standards was outlined, the cases of polysemantic kind of consept-standards realization were ascertained, also there were cases of synonymy and enantiosemia of comparative phraseologisms discovered.
Keywords: verbalizator; ethnic worldview; standard; comparative phraseological units; componen